Effect of oxygen heteroatom on sensor-cyanide anions binding - R Rahmawati; Fara Dwirani Sofia (Acta Chimica Asiana, 2022)
The study aims to analyze the effect of heteroatom replacement on benzimidazole derivative chemosensor compounds on the ability to form hydrogen bonds with anions. In this case, the N heteroatom in the benzimidazole derivative sensor compound (S1) is replaced with the O heteroatom to become a benzoxazole derivative sensor compound (S3). Calculating the energy of the molecules involved in the electron level gives the following results: replacing heteroatoms with more electronegative atoms increases the HOMO energy of the sensor molecules, making the sensor more reactive to anions and strengthening the binding of the sensor with cyanide anions.